The liability of external auditor: how it is determined / Mohd Redzwan Salleh - Salleh, Mohd Redzwan (1993)
Many of us will think auditor as a person who knows about the accountancy profession. Many of us perceive that the auditor is a qualified person arid his work cannot be questioned., But how far it is true and to what extent he is liable towards their job is still a matter of question. Therefore this project paper will try to discuss and determine the extent of the liability of this profession.